Turnover in companies: internal and external reasons (Revista Brasileira de Contabilidade e Gestão, 2016)
Currently, it is evident that the growth and development of new companies in the textile industry is directly linked to the growth of the turnover subject, that is, the number of employees entering and leaving the companies, which, when expressive, can harm the organization’s growth and progress. Since this sector depends on a significant number of employees, they need to present characteristics that attract new people or even encourage their own employees to stay in the company for a long time. Due to the competitiveness between companies and the need to maintain a stable and satisfied staff within the company, identifying whether the reasons causing the turnover are from internal or external factors is important, so that the company is aware of them to minimize or even eliminate them. The aim of this article is to identify and demonstrate the main reasons for turnover. The initial results show that one of the main reasons listed is the satisfaction at work and the quality of life provided in the work environment, so we can observe that the issue of remuneration is not the primary factor.
Keywords: turnover; internal factors; external factors